Numerical Simulation of Hydrodynamic Pressure on Concrete Bridge Pier in Water from a Series of Model Tests. Issue 2 (October 2020) - Qin, Yifang; Tao, Xiaxin; Liu, Haiming; Tao, Zhengru
Abstract: To develop numerical procedure to simulate hydrodynamic pressure on concrete bridge pier in water, finite element models are built by software ADINA with the same sizes and material properties in a set of shaking table tests in this paper. The results our numerical simulations show that the all pressures on the three piers decrease with the submerged depth at the similar rate as test data shows, and the mean values of the ratios of numerical results to the test data are mainly from 0.8 to 1.0. The pressures on piers with different section shapes at same depth are varied and the relative order is not stable. The finding is similar to that from the test data, but different to the shape coefficient values provided in some seismic design codes of highway bridges. It suggests to check what kind of horizontal variation of hydrodynamic pressures at same depth level is there from the center to the edges. The pressures with reflected wave are approximately half to two third of those without reflected wave. It means that the reflection effect reduce the hydrodynamic pressure on bridge pier obviously. The effectivity of the absorbing stuff on the side walls of the tank in the tests must be improved, or a new way to replace this kind of measure must be worked out.